A novel ZVS buck converter topology for VRM applications - Jinbin Zhao (2011 6th IEEE Conference on Industrial Electronics and Applications, 2011)
The paper presents a novel ZVS buck converter topology. The proposed topology solves narrow duty cycle and hard switching problems of conventional buck converter in lower output voltage and higher output current. At the same times, the voltage stresses across main switches are also clamped at input voltage. In the topology, an adjustable inductor and a resonant capacitor are used to reduce charge voltage and extend the discharge time of filter inductor to achieve above target. To demonstrate the results, detailed steady-state analysis is presented. Finally, a 48V/1V, 10A simulation prototype is built to verify the theoretical analysis and shows the significant advantages.